The Situation in Hungary (Concluded). Special Report of the Special Committee on the Problem of Hungary (Concluded). Plenary Meeting 787th, Thirteenth Session , Agenda Item 69 - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. General Assembly Continuation from the previous session. General Assembly: Plenary Meeting 786th: Thirteenth Session: Official Records: Special Report of the Special Committee on the problem for Hungary A/3849. The new draft resolution was adopted by 54 to 10 with 15 abstentions. According to the Nepalese representative, the Hungarian problem is not a Cold War issue, but of universal international importance, because "what happened to the people of Hungary in the fall of 1956 may happen to the people of a small country anywhere in the world". Strong objections against the resolution were expressed by the official Hungarian representative Mr. Péter, who believes that Hungarian question is used as a key weapon in the "embittered atmosphere" of the Cold War.